Chemotherapeutic Compounds Targeting the DNA Double-Strand Break Repair Pathways: The Good, the Bad, and the Promising - Jekimovs, Christian; Bolderson, Emma; Suraweera, Amila; Adams, Mark; O’Byrne, Kenneth J.; Richard, Derek J. (Frontiers in Oncology, 2014)
The repair of DNA double-strand breaks is a critical cellular mechanism that exists to ensure genomic stability. DNA double-strand breaks are the most deleterious type of insult to a cells genetic material and can lead to genomic instability, apoptosis or senescence. Incorrectly repaired DNA double-strand breaks have the potential to produce chromosomal translocations and genomic instability, potentially leading to cancer. The prevalence of DNA double-strand breaks in cancer due to unregulated growth and errors in repair opens up a potential therapeutic window in the treatment of cancers. The cellular response to DNA double-strand breaks is comprised of two pathways to ensure DNA breaks are repaired: homologous recombination and non-homologous end joining. Identifying chemotherapeutic compounds targeting proteins involved in these DNA repair pathways has shown promise as a cancer therapy for patients, either as a monotherapy or in combination with genotoxic drugs. From the beginning, there have been a number of chemotherapeutic compounds that have yielded successful responses in the clinic, a number that have failed (CGK733 and Iniparib) and a number of promising targets for future studies identified. This review looks in detail at how the cell responds to these DNA double-strand breaks and investigates the chemotherapeutic avenues that have been and are currently being explored to target this repair process.